2020
DOI: 10.3390/ijerph17155591
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about the Harmfulness of Heated Tobacco Products Compared with Combustible Cigarettes and Their Effectiveness for Smoking Cessation among Korean Adults

Abstract: Heated tobacco products (HTPs) have been widely used in Korea since their introduction in 2017. In this study, we investigated the perceptions of their relative harmfulness and smoking cessation effects. We performed an online survey in 7000 Koreans in 2018 (2300 males and 4700 females aged 20–69 years) by matching their age, sex, and provincial distribution. To investigate the factors causing HTPs to be perceived as less harmful than combustible cigarettes (CCs) and helpful for smoking cessation, we used mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…However, the marketing by tobacco companies has led to a positive attitude towards HTPs among tobacco product users. Although many smokers understand that e-cigarettes or HTPs are not risk-free, they use e-cigarettes or HTPs due to their belief that there are health benefits over CCs 11 . The positive attitude toward HTPs is one of the independent predictors of initiation or continuation of HTP use.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the marketing by tobacco companies has led to a positive attitude towards HTPs among tobacco product users. Although many smokers understand that e-cigarettes or HTPs are not risk-free, they use e-cigarettes or HTPs due to their belief that there are health benefits over CCs 11 . The positive attitude toward HTPs is one of the independent predictors of initiation or continuation of HTP use.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies from various countries suggest that HTP poly-users may have higher nicotine dependence and are likely to underestimate their harmful effects to a greater extent than HTP-only users 20,[23][24][25][26] . A recent study of Korean adults showed that HTP-only users and polyusers of tobacco products were more likely to perceive HTPs as less harmful than CCs than cigarette-only smokers 11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Moreover, exclusive HTP users are more likely to report that HTP is helpful for smoking cessation than dual users are. 26 Exclusive HTP users might have higher motivation and awareness to quit using tobacco than traditional smokers, which might contribute to the high program adherence rate.…”
Section: Discussionmentioning
confidence: 99%